Understanding the effect of government attitudes on voluntary tax compliance in Nigeria - Yahaya, Lawan; Turmin, Siti Zaidah; Johari, Jalila; Osman, Mohammad Noor Hisham (Human Resource Management Academic Research Society, 2022)
An effective government’s performance is indicated by; high levels of efficiency, bureaucratic quality, the rule of law and the fight against corruption. This paper aimed to examine the effect of government attitudes on voluntary tax compliance in Nigeria. The study distributed 384 questionnaires to self-employed taxpayers in Nigeria, out of which 296 questionnaires were successfully returned. An analysis was conducted incorporating structural equation modelling using the SmartPLS 3.3 software application 3.3 to derive the measurement and structural model of the analysed result. The results showed that government effectiveness positively and significantly affected voluntary tax compliance. Additionally, the findings revealed a positive and significant effect between tax authority transparency and voluntary tax compliance. Further findings showed that government attitude was positively and significantly related to voluntary tax compliance. Therefore, the present study recommends that the government improve its attitudes toward efficiency and transparency in tax and governance to improve voluntary taxpayer compliance with Nigeria's tax authorities.